Bibliografska predstavitev Glasbene šole Jesenice - Jamar, Nina (Knjižnica, 2021)
Purpose: The publishing activity at the Music School Jesenice (MSJ) and the articles published about it in local periodical publications are presented. Methodology/approach: Publications and articles are presented in two separate bibliographies. Results: The bibliography of publications of the MSJ and the bibliography of articles about the MSJ were prepared. First bibliography includes 111 units and the second bibliography includes 199 units. Research limitation: The publishing activity at the MSJ started more intensively after 2003, therefore the bibliography includes publications published by MSJ from the be-ginning of 2003 till the end of 2020. The inclusion of articles about MSJ into COBIB database started systematically in the year 2017, therefore the bibliography includes articles published about MSJ from the beginning of 2017 till the end of 2020. The publications published by MSJ before 2003 and the articles published about MSJ before 2017 are not included in the bibliographies. Originality/practical implications: With publishing activity and the inclusion of publications published by MSJ and articles published about MSJ in local serial publications in the system COBISS, we wanted to make sure that the memory on activities at MSJ (performances, concerts and other activities) will remain. Therefore, we decided that these publications and articles deserve more detailed presentation.
Keywords: Bibliografije; bibliographies; Glasbena šola Jesenice; Glasbene šole; Jesenice; music schools; school libraries; Šolske knjižnice